Comparative development of five sympatric coastal Fundulid species from the northern Gulf of Mexicoa - Lang, Erik T.; Peterson, Mark S.; Slack, William T. (Zootaxa, 2011)
There are five coastal fundulid species in the northern Gulf of Mexico (nGOM) including Fundulus jenkinsi, which is recognized within all states from Louisiana through Florida and federally as a Species of Concern. This particular fundulid was listed because of a perceived linkage to salt marsh habitat, only scant data available on its ecology, and salt marsh habitat being altered throughout its range. Little is known about the life history of this coastal killifish, but a detailed diagnostic key of the early life stages of select members of Fundulidae can provide the foundation needed to accurately identify this rare species in need of conservation. Larval and postlarval stages of select members of the family Fundulidae along the east coast of the U.S. have been described and compared among species. We illustrated various stages of coastal Fundulus spp. and Adinia xenica in the northern GOM and quantified morphometric and meristic characters. Total length, head length, body depth, caudal peduncle width, snout length, eye diameter, anal and dorsal fin counts, and diagnostic pigment patterns were compared among species. The first branch of our dichotomous key utilized the number of branchiostegal rays to separate young fundulids (< 15 mm TL) into two groups that can then be identified by selected pigment patterns, morphometrics, and meristics.